A New Class of Time-Meridian Surfaces of Biharmonic - Particles and its Lorentz Transformation in Heisenberg Spacetime - Korpinar, Talat; Turhan, Essin (Springer/Plenum Publishers, 2015)
The present study deals with time-meridian surfaces and its Lorentz transformations in a new spacetime Heisenberg spacetime. We give a geometrical description of time-meridian surfaces around biharmonic particle in Finally, we obtain Lorentz transformations this particles.
Keywords: Time-meridian surface; Energy; Bienergy; Heisenberg group; Faraday tensor; Lorentz transformations